Determinants of Know Your Customer (KYC) Compliance among Commercial Banks in Kenya - Arasa, Robert (Journal of Economics and Behavioral Studies, 2015)
KYC conformity entails the creation of auditable evidence of due diligence activities, in addition to the need for customer identification. There is necessity for financial institutions to validate that their customers are not or have not been involved in illegal activities such as fraud, money laundering or organized crime in order to meet KYC conformity requirements. This study examines factors that determine the level of compliance with KYC requirements by commercial banks in Kenya. Specifically, this study investigates the effect of customer characteristics, staff competency, information communications technology infrastructure and bank size on the level of KYC compliance requirements. The study used descriptive research design. The target population of this study was the top and middle level officers who are directly involved in the day-today operations of the commercial banks. For purposes of this study a descriptive survey design was employed. The target population was 43 commercial banks and 1 mortgage finance firms operating in Kenya. Target respondents comprised of top and middle level involved in the day-to-day institution’s operations. Questionnaire was used as the main data collection instrument. To address the objectives of the study, descriptive and inferential analysis techniques were utilized. Regression analysis was employed to ascertain the relationships between KYC compliance and the four variables of interest in this study. Computations of coefficient of determination indicates that four independent variables that were studied, explain 78.3 percent of the commercial banks compliance level with KYC requirements in Kenya, implying that 21.7 percent could be explained by other factors not examined in this study. Study findings reveal that customer characteristics are a key determinant of KYC compliance, small banks are not capable of meeting KYC compliance cost and that staff attitudes and physical facilities affect customer service and effective KYC procedures compliance. Regression analysis further reveals that there is a significant relationship between the four variables and KYC compliance level. Finally the study recommends that ICT is a useful tool that could be used to enhance compliance with KYC requirements.